Keanekaragaman Echindodermata Berdasarkan Tipe Substrat Di Pulau Tidung Kepulauan Seribu - Fitri Andriyani; Muhammad Saiful; Nada Syifa Azahra; Safina Zahira; Rindy Serlina; Rusdi (Risenologi, 2021)
The purpose of this study was to determine the biodiversity of Echinodermata on Tidung island. This study was conducted on February 2019 using purposive sampling method. Data collection was performed using belt transect method and data were analyzed quantitatively by calculating Echinoderm’s abundance relativity index and species diversity index and compare the data on each substrate. Based on observations of Echinoderms species diversity on Tidung island, belongs to low to moderate level with a value of 0.8269 - 1.0057 and abundance is mostly found at station 2 with a value of 52.5%, of Ophiomastix sp. totaled 21 individuals and salinity at station 2 was 28%